Stephanie Dinkins On Love & Data - Mitra, Srimoyee (University of Michigan Press, 2024)
Stephanie Dinkins is renowned for her critical investigations into artificial intelligence and machine learning systems as they intersect race, gender, and our future histories. By using her training in documentary practices as a photo-based artist, she creates inclusive platforms for dialogue and action toward building technological ecosystems and datasets that are equitable, accessible, and transparent. Her immersive installations, community-based workshops, and public talks seek audience participation and engagement in a way that pushes the boundaries of new media and socially engaged art practices in the 21st century. Stephanie Dinkins: On Love & Data brings together nationally renowned curators and theorists who draw from methodologies of art criticism, social practice, new media theory, and critical studies to offer an in-depth analysis of key installations in Dinkins's survey exhibition. The book also includes an important essay by Stephanie Dinkins on her concept of Afro-now-ism in which she expands on her theoretical framework and positionality as a Black new media artist in the 21st century. Dinkins's artistic research transcends the boundaries of visual art to challenge and expose the bias and inequities of caste, race, and gender, which are encoded within digital systems on which governance, healthcare, and security infrastructures in the United States are based.